Cultura de preservação: o patrimônio histórico na cidade de Caçapava - SP - Barreira, Maria Eneida [UNIFESP] (2019)
This work aims to present some general questions about historical heritage, especially in urban space, as an act of preservation of identity, in an international context and also in relation to Brazil and the State of São Paulo. In particular, it is focused in the city of Caçapava, in the Paraíba Valley, with an analysis of the present preservation conditions, through a comparative exercise between the photographs made for the survey carried out in 1978 by the Architect Gustavo Neves da Rocha Filho, on one side; and photographs taken in the current context of the city, on the other.